Near-zero restrained shrinkage polymer concrete incorporating ceramsite and waste rubber powder. (July 2020) - Shen, Yinong; Ma, Xiaobing; Huang, Jiantao; Hao, Fan; Lv, Jianfu; Shen, Manlin
Abstract: In this study, we reduced the restrained shrinkage of lightweight polymer concrete (LWPC) containing waste rubber powder (WRP) to develop a novel low-shrinkage LWPC for use in wet flue gas desulfurization (WFGD) or other high-temperature and strongly corrosive environments. We investigated the effects of ceramsite aggregate and WRP (0%, 2.5%, 5.0% and 7.5% of binder) on restrained shrinkage and the microstructure of polymer concrete (PC). The experimental results indicate that restrained shrinkage in PC with ceramsite aggregate and WRP is significantly less than that of PC with crushed stone aggregate. Unusual stress relaxation behavior of LWPC was observed. When WRP reached 7.5% of binder, the value of restrained shrinkage was nearly zero. Ultra-depth three-dimensional microscopy (UDTDM), X-ray computed tomography (XCT), and scanning electron microscopy (SEM) were used to characterize PC properties for the determination of stress relaxation mechanisms.